On Strongly Associative (Semi)Hypergroups - Morteza Jafarpour; Fatemeh Jantani; Violeta Leoreanu (Journal of the Indonesian Mathematical Society, 2017)
In this paper we introduce the notion of a strongly associative hyperoperation that we call SASS and obtain new class of semihypergroups....